Comparative Transcriptome Profiling of Maytenus ilicifolia Root and Leaf - Santoni, Mariana Marchi [UNESP]; de Lima, João Vítor Félix [UNESP]; Bicalho, Keylla Utherdyany; de Souza Moreira, Tatiana Maria [UNESP]; Valentini, Sandro Roberto [UNESP]; Furlan, Maysa [UNESP]; Zanelli, Cleslei Fernando (Springer Nature, 2021)
Plants produce a wide variety of compounds called secondary metabolites (SMs), which are extremely important for their survival. SMs have also medicinal applications, but as chemical synthesis is not economically viable, plant extraction is the mainly option. Different biotechnology strategies are applied to improve the yield of bioproduction of these compounds, but commonly without the desired results due the limited knowledge of biosynthetic and regulatory pathways. Maytenus ilicifolia, a traditional Brazilian medicinal plant from Celastraceae family, produces in both root and leaves three main classes of SMs: sesquiterpenics, flavonoids and quinonemethides. In this study, four cDNA libraries were prepared from root and leaf tissues. The de novo transcriptome included 109,982 sequences that capture 92% of BUSCO orthologs, presented an average length of 737bp and a GC content about 42% of. Function annotation analysis identified homology for 44.8% of the transcripts. Moreover, 67,625 sequences were commonly expressed in both tissues, while 1,044 and 1,171 were differentially expressed in root and leaf, respectively. In terms of SM, enzymes involved in “monoterpenoid biosynthesis” and “isoflavonoid biosynthesis were identified in root while “flavonoid biosynthesis” and “Biosynthesis of alkaloids” in leaf.
Keywords: De novo assembly; Metabolic pathways; RNA-Seq